Theme-Rheme Organization of Background Section in Research Proposal Introduction - Desih Nurdianti; John Pahamzah; Yusti Fargianti (Journal of Linguistics, Literacy, and Pedagogy, 2022)
This study aimed to investigate what thematic development pattern frequently applied on students’ proposal year 2019 seen from three levels of achievement: low, middle, and high. Qualitative research as a method by implementing content analysis. The data of the study were 6 students’ proposal from low, middle, and high level of achievement. The steps in analyzing the data are first: taking texts written by the students, second: reading the texts and segmenting each  text into clauses, third: identifying theme and rheme of each clause of the students’ texts, fourth: identifying thematic development pattern of the students’ texts by using thematic development pattern proposed by Danes (1974), fifth: consulting the identified thematic development pattern to the experts, and sixth: calculating the amount of the occurrence of each thematic development pattern. The result shows that Constan Theme Progression (CTP) became the most applied pattern on high achievers’ text with the total number of occurrences 7 (63%). Constan Theme Progression (CTP) also became the most applied pattern on middle achievers’ text with the total number of occurrences 5 (55%) as well as on low achievers’ text, Constant Theme Progression became (CTP) the most applied pattern with the total number of occurrences 6 (50%). In conclusion, the students at University of Sultan Ageng Tirtayasa academic year 2019 who learn English as a foreign language mostly applied Constant Theme Progression in their research proposal.